Analisis Penambahan Bioethanol dan Oktan Booster pada Bahan Bakar Pertamax terhadap Daya dan Torsi Sepeda Motor 4-Langkah - Pamungkas, Rizky Romadhon Putra; Listiyono, Listiyono (Lembaga Yasin AlSys, 2024)
There are various methods to improve vehicle performance, including by blending fuels. In addition to bioethanol that can increase octane rating, there is the use of additives in vehicle fuels that are known to increase octane rating. With the addition of additives such as octane boosters and bioethanol, it is expected to increase the degree of ignition, reduce knocking, achieve more complete combustion, and automatically increase vehicle power.This study aims to analyze the power and torque of a four-stroke motorcycle by considering the addition of bioethanol and octane boosters to Pertamax fuel. Experimental method was used with variation of bioethanol concentration and octane booster in fuel as test parameters. This study provides insight into the potential for power improvement in the use of Pertamax fuel on four-stroke motorcycles through the addition of bioethanol and octane booster. The implications of these findings can serve as a basis for the development of more efficient and sustainable fuels for four-stroke motorcycles.